2018
DOI: 10.1002/mabi.201800366
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide‐Loaded pH‐Responsive Nanoparticles Alleviating Tumor Acidosis to Enhance Chemotherapy Effects

Abstract: Carbonic anhydrase IX (CA IX), over‐expressed on cancer cells, catalyzes CO2 to bicarbonate and protons, contributing to the acidic extracellular pH (pHe), which enhances the multidrug resistance of tumor cells. Therefore, alleviating tumor acidosis would greatly improve the outcome of chemotherapy. This work fabricates acetazolamide (ACE)‐loaded pH‐responsive nanoparticles (ACE‐NPs), which are quickly disintegrated in an acidic solution (pH 6.8), resulting in a quick release of ACE from these NPs to inhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Except one study using silica nanoparticles coated with the anti-CA IX MAb M75 [62], all other studies exploited carbonic anhydrase inhibitors. As CA inhibitors are principally acting towards diverse CA isoforms due to similarities in their active sites, selectivity to CA IX was conferred by diverse carriers [45], gold nanoparticles [46], pH-responsive nanoparticles [47], polymer-based photodynamic nanoinhibitor particles [48]. However, the approaches using inhibitors principally differ from the approach using monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except one study using silica nanoparticles coated with the anti-CA IX MAb M75 [62], all other studies exploited carbonic anhydrase inhibitors. As CA inhibitors are principally acting towards diverse CA isoforms due to similarities in their active sites, selectivity to CA IX was conferred by diverse carriers [45], gold nanoparticles [46], pH-responsive nanoparticles [47], polymer-based photodynamic nanoinhibitor particles [48]. However, the approaches using inhibitors principally differ from the approach using monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated the modification of screen-printed carbon electrodes by assembling graphene oxide to obtain electrochemical immunosensors with immobilized antibodies specific to mucin 1, which is a well-known tumor marker for a variety of malignant tumors [44]. Efforts to detect or target CA IX have been mostly focused on development of diverse nanoparticles decorated by inhibitors of Carbonic anhydrases with modifications conferring selectivity towards CA IX and/or other cell surface isoforms [45,46,47,48]. These approaches require access to active site of the enzyme, whereas the antibodies can bind CA IX even in an inactive state.…”
Section: Introductionmentioning
confidence: 99%
“…24 The imine bond is easily disintegrated in an acidic solution (pH ¼ 6.8). 25 Thus, if exosome membrane is conjugated chemotherapy drugs with hydrazone bond, the cleavage of the imine bond triggered by acidic TME would result in quick release of drugs in the tumor site. Next, hypoxia is another the distinct hallmarks of TME that induce irreversible tumor metastasis, as well as inict hypoxiaassociated resistance.…”
Section: Introductionmentioning
confidence: 99%
“…More details can be found in chapter 2; a review addressing the position of PHD enzymes in hallmarks of atherosclerosis. In short, PHD proteins form a potentially interesting target in atherosclerosis, as HIF1 was already shown to affect plaque development in several cell types [92][93][94]. Furthermore, previous studies uncovered a role of isoform specific PHD signaling in NF-κB activation [95][96], fibrosis [97][98][99][100] and lipid/glucose metabolism [101], which are all instrumental in atherogenesis, emphasizing the possible impact of PHDs in plaque development.…”
Section: Effectors Of Hypoxia: Hif and Phd Proteinsmentioning
confidence: 99%
“…Thirdly, CAIX targeting nanoparticles are under investigation [91], although this is still in a pre-clinical testing stage. Nevertheless, results from in vivo mouse models are promising, showing reduced tumor growth and higher survival rates in animals treated with CAIX inhibiting nanoparticles [92]. Altogether, multiple CAIX inhibiting compounds are being developed as we speak.…”
Section: Is Caix a Viable Treatment Target To Combat Atherosclerosis?mentioning
confidence: 99%